2017
DOI: 10.18632/oncotarget.18493
|View full text |Cite|
|
Sign up to set email alerts
|

MMP-3 gene polymorphisms are associated with increased risk of osteoarthritis in Chinese men

Abstract: Osteoarthritis (OA) is the most common late-onset degenerative joint disease., It is characterized by progressive degradation of articular cartilage. We investigated the association between OA occurrence and single nucleotide polymorphisms (SNPs) in the matrix metalloproteinase-3 (MMP-3) gene involved in the breakdown of extra-cellular matrix proteins. The study included 100 male OA patients and 197 healthy men from the north area of China. Eight MMP-3 SNPs were genotyped. Odds ratios (ORs) with 95% confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…ADAMTS4 and ADAMTS5, also known as aggrecanase-1 and aggrecanase-2, are two members of ADAMTSs family and have been shown to degrade the cartilage proteoglycanaggrecan [ 12 , 13 ]. A series of studies have suggested that variants of genes encoding ECM degrading enzymes were related with OA, such as matrix metalloproteinase (MMP)-1 [ 14–18 ], MMP-3 [ 14 , 19 , 20 ] and MMP-9 [ 17 ]. Strong associations between MMP-3, MMP-9 polymorphisms and risk of lumbar disc degeneration (LDD) were also indicated [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…ADAMTS4 and ADAMTS5, also known as aggrecanase-1 and aggrecanase-2, are two members of ADAMTSs family and have been shown to degrade the cartilage proteoglycanaggrecan [ 12 , 13 ]. A series of studies have suggested that variants of genes encoding ECM degrading enzymes were related with OA, such as matrix metalloproteinase (MMP)-1 [ 14–18 ], MMP-3 [ 14 , 19 , 20 ] and MMP-9 [ 17 ]. Strong associations between MMP-3, MMP-9 polymorphisms and risk of lumbar disc degeneration (LDD) were also indicated [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinase-1 (MMP-1)is produced by synovial cells, chondrocytes, and osteoblasts, which can degrade extracellular matrix collagen and mediate cartilage destruction [7][8]. The expression of MMPs has been shown to be affected by single nucleotide polymorphisms (SNPs) occurring in MMP gene promoters [9].These promoter polymorphisms have allele-speci c effects on the regulation of MMP gene transcription and are associated with the development and/or progression of some common diseases [3][4][5]. Matrix metalloproteinases secreted from chondrocytes are the main enzymes responsible for pathological cartilage destruction [6].Expression of MMP-1 is low in normal cells that leads to healthy cartilage remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Knee OA is a common joint disease which is characterized by degeneration of the articular cartilage and subsequent subchondral bone changes. Knee OA is a combined result of environmental and genetic factors, while genetic factors account for nearly 50% of the risk of OA development [2].Although the underlying mechanisms remain unknown, many studies have shown that the occurrence of knee osteoarthritis is related to cytokines, including Matrix metalloproteinases (MMPs) family [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinase-1 (MMP-1)is produced by synovial cells, chondrocytes, and osteoblasts, which can degrade extracellular matrix collagen and mediate cartilage destruction [7][8]. The expression of MMPs has been shown to be affected by single nucleotide polymorphisms (SNPs) occurring in MMP gene promoters [9].These promoter polymorphisms have allele-specific effects on the regulation of MMP gene transcription and are associated with the development and/or progression of some common diseases [3][4][5]. Matrix metalloproteinases secreted from chondrocytes are the main enzymes responsible for pathological cartilage destruction [6].Expression of MMP-1 is low in normal cells that leads to healthy cartilage remodeling.…”
Section: Introductionmentioning
confidence: 99%